Does long-term fire suppression impact leaf litter breakdown and aquatic invertebrate colonization in pine flatwoods wetlands? - Chandler, Houston C.; Colón-Gaud, J. Checo; Gorman, Thomas A.; Carson, Khalil; Haas, Carola A. (PeerJ, 2021)
Ephemeral wetlands are commonly embedded within pine uplands of the southeastern United States. These wetlands support diverse communities but have often been degraded by a lack of growing-season fires that historically maintained the vegetation structure. In the absence of fire, wetlands develop a dense mid-story of woody vegetation that increases canopy cover and decreases the amount of herbaceous vegetation. To understand how reduced fire frequency impacts wetland processes, we measured leaf litter breakdown rates and invertebrate communities using three common plant species (Longleaf Pine (Pinus palustris), Pineland Threeawn Grass (Aristida stricta), and Black Gum (Nyssa sylvatica)) that occur in pine flatwoods wetlands located on Eglin Air Force Base, Florida. We also tested whether or not the overall habitat type within a wetland (fire maintained or fire suppressed) affected these processes. We placed leaf packs containing 15.0 g of dried leaf litter from each species in both fire-maintained and fire-suppressed sections of three wetlands, removing them after 103–104 days submerged in the wetland. The amount of leaf litter remaining at the end of the study varied across species (N. sylvatica = 7.97 ± 0.17 g, A. stricta = 11.84 ± 0.06 g, and P. palustris = 11.37 ± 0.07 g (mean ± SE)) and was greater in fire-maintained habitat (leaf type: F2,45 = 437.2, P < 0.001; habitat type: F1,45 = 4.6, P = 0.037). We identified an average of 260 ± 33.5 (SE) invertebrates per leaf pack (range: 19–1,283), and the most abundant taxonomic groups were Cladocera, Isopoda, Acariformes, and Diptera. Invertebrate relative abundance varied significantly among litter species (approximately 39.9 ± 9.4 invertebrates per gram of leaf litter remaining in N. sylvatica leaf packs, 27.2 ± 5.3 invertebrates per gram of A. stricta, and 14.6 ± 3.1 invertebrates per gram of P. palustris (mean ± SE)) but not habitat type. However, both habitat (pseudo-F1,49 = 4.30, P = 0.003) and leaf litter type (pseudo-F2,49 = 3.62, P = 0.001) had a significant effect on invertebrate community composition. Finally, this work was part of ongoing projects focusing on the conservation of the critically imperiled Reticulated Flatwoods Salamander (Ambystoma bishopi), which breeds exclusively in pine flatwoods wetlands, and we examined the results as they relate to potential prey items for larval flatwoods salamanders. Overall, our results suggest that the vegetation changes associated with a lack of growing-season fires can impact both invertebrate communities and leaf litter breakdown.
Keywords: Ambystoma bishopi; Ephemeral wetlands; Reticulated Flatwoods Salamander; Leaf packs; Longleaf Pine; Wiregrass